State-of-the-Art of CSR Design for Novel Applications Trend - Valdecir J. De Paris; Marco di Benedetto; Gierri Waltrich; Alessandro Lidozzi; Luca Solero (IEEE Open Journal of Industry Applications)
Among the converters currently employed for ac–dc conversion, diode rectifiers (DRs) and voltage source rectifiers are the most prevalent due to their accessibility, cost-effectiveness, and efficiency. However, current source rectifiers (CSRs) present several advantages, such as short-circuit protection, step-down capabilities, minimal output current ripple, and the elimination of dc bus capacitors. These features can lead to a reduction in overall size and an enhancement in power quality, although CSRs are often associated with higher conversion losses. Recent advancements in applications that can leverage the benefits of CSRs, along with the development of new devices to improve their efficiency, have produced renewed interest in this configuration. This article aims to review the design parameters of CSR components, modulation schemes, and control strategies, while also conducting a loss analysis using both established literature methods and innovative approaches developed by the authors. In addition, a comparison with other topologies is presented, illustrating that in certain applications and conditions, CSRs can be a compelling choice. Thus, rather than focusing on a specific aspect of CSRs, this article provides a comprehensive overview of the topic, offering practical insights for engineers.